Extremely Difficult Paths of Polish Educational Reforms between 1989 and 2014 - Kucha, Ryszard (International Dialogues on Education Journal, 2015)
In the 25 years after the events of 1989, a mismatch between the system of education and the system of market economy has become a universal phenomenon in Poland as one of the European countries. There are also signs indicating the educational expansion does not promote the role of the individual in the process of socio-economic development of the society. As a result, the younger generation experiences a great dissatisfaction and frustration generated by their difficulties in fulfilling their educational, social, and professional aspirations and expectations. This paper provides a review and critique of the educational strategies implemented by bureaucratic central and local administration of the last 25 years of Polish society life.